Accuracy of three global positioning systems for determining speed and distance parameters in professional soccer - Schmidt, M.; Nolte, K.; Kolodziej, M.; Ulbricht, A.; Jaitner, T. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
GPS technology is widely used to design training programs and control training based on objective performance data. Accuracy of that data is crucial, especially when comparing different manufacturers. The validity and reliability of different devices have been examined in several studies. However, there is limited information regarding the concurrent accuracy of different devices in the same applied setting. This study investigates the accuracy of three commercially GPS devices in speed and distance measures during a soccer-specific setting in comparison to a reference system. 25 youth U-19 male professional soccer players completed a soccer-specific circuit three times in total, wearing each GPS device once. Performance data as provided by the three manufacturer`s algorithms were compared against a simultaneously recorded 3D-motion capture system (14 cameras, 100 Hz). Intraclass correlation coefficients show poor to excellent accuracies for all systems during high speed running. Distances covered with lower velocities are estimated with poor to excellent accuracy. Maximum velocity is underestimated by two of the systems, whereas the other one overestimates maximum velocity. Large confidence intervals as well as limits of agreement indicate high uncertainties of the described accuracies. This should be considered carefully, because measurement errors potentially lead to misestimating of player load.